Existence and multiplicity of solutions for elliptic equations with singular growth - Yasmina Nasri; Ali Rimouche (Electronic Journal of Differential Equations, 2016)
In this article, we consider an elliptic problem with singular and critical growth. We prove the existence and multiplicity of solutions for the resonant and nonresonant cases.